Immunotherapy for osteosarcoma: Fundamental mechanism, rationale, and recent breakthroughs. (1st March 2021) - Chen, Chenglong; Xie, Lu; Ren, Tingting; Huang, Yi; Xu, Jie; Guo, Wei
Abstract: Osteosarcoma (OS) is the most common primary malignancy of the bone and has a high propensity for local invasion and metastasis. Although combining surgery with chemotherapy has immensely improved the outcomes of osteosarcoma patients, the prognosis of metastatic or recurrent osteosarcomas is still unsatisfactory. Immunotherapy has proven to be a promising therapeutic strategy against human malignancies and improved understanding of the immune response to OS, and biomarker development has increased the number of patients who benefit from immunotherapies in recent years. Here, we review recent advances in immunotherapy in osteosarcoma and discuss the mechanisms and status of immunotherapies in both preclinical and clinical trials as well as future therapies on the horizon. These advances may pave the way for novel treatments requisite for patients with osteosarcoma in need of new therapies. Highlights: Immune response affects osteosarcoma both locally and systemically. There are many immune-based basic studies and clinical trials ongoing, but immunotherapy is not that effective on osteosarcoma. Despite the potential of immunotherapy in osteosarcoma, some challenges remain, and more attention should be paid to other immune cells but not just T cells in TME.